2007
DOI: 10.1161/circulationaha.106.677914
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of Complement Inhibition With Soluble Complement Receptor 1 (TP10) During Cardiac Surgery

Abstract: and the TP10 Cardiac Surgery Study GroupBackground-TP10, a potent inhibitor of complement activation during cardiopulmonary bypass (CPB) has been shown to significantly reduce the incidence of death and myocardial infarction (MI) in high-risk male patients undergoing cardiac surgery. However, the effect of TP10 in females was undefined because of the limited number of females studied. To examine the possibility of a gender effect, this phase 2 multi-center trial was undertaken to determine whether TP10 would a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 26 publications
(21 reference statements)
0
23
0
Order By: Relevance
“…However, super-physiologic singledose treatment with sCR1 has been used in .500 patients (infants and adults) undergoing a variety of cardiac surgeries or after myocardial infarctions to arrest complement activation. [23][24][25][26] These studies showed that sCR1 was well tolerated with no adverse events clearly or consistently associated with its use. Importantly, the possible development of anti-sCR1 antibodies was monitored but never observed in .350 patients.…”
mentioning
confidence: 81%
“…However, super-physiologic singledose treatment with sCR1 has been used in .500 patients (infants and adults) undergoing a variety of cardiac surgeries or after myocardial infarctions to arrest complement activation. [23][24][25][26] These studies showed that sCR1 was well tolerated with no adverse events clearly or consistently associated with its use. Importantly, the possible development of anti-sCR1 antibodies was monitored but never observed in .350 patients.…”
mentioning
confidence: 81%
“…Lazar et al studied the effects of TP10 in high-risk patients undergoing cardiac surgery, but even if complement activation was effectively suppressed by TP10, there was no reduction in the clinical composite primary endpoint (Lazar et al, 2004). However, there was a reduction in mortality and myocardial infarction size in males but not in females (Lazar et al, 2004;Lazar et al, 2007), suggesting that the effects of TP10 may be gender-related. These observations have not been further explored.…”
Section: Complement Inhibition In Coronary Heart Diseasementioning
confidence: 99%
“…The TP10 group showed a lower primary endpoint event rate by 30% only in male patients. In a follow-up study of 297 female patients randomized to treatment with TP10 or placebo, it was shown that TP10 suppressed complement activation but did not reduce the incidence of death or MI by 28 days after surgery (Lazar et al 2007). A possible reason for this lack of difference is that the number of adverse events in the control arm of this trial was quite low to begin with, at 17%.…”
Section: Therapymentioning
confidence: 86%